Learning fundamental academic english via MOOC / Turisiana Ahmad Buhari ...[et al.] - Ahmad Buhari, Turisiana; Ab Rahman, Doreen Azlina; Mohd Aris, Nurbaya; Sulaiman, Shairah Hana (Universiti Teknologi MARA Shah Alam, 2018)
Massive Open Online Course (MOOC) has since its launch provided a diverse choice of learning courses and modules. Openlearning.com claims to have over 4000 MOOCs from around the world, making it an indispensable place to gain knowledge other than the traditional classroom or formal education. This growing number of MOOCs means that the mass has the interest to learn various subjects the virtual way at their own pace and comfort. Despite this increasing number, there are also concerns that not all subjects and skills can be delivered and taught online. Like many language subjects, Academic English is a challenging course to teach and learn. This is due to the specific skills involved in which requires constant guidance on how to deliver best. Hence, Fundamental Academic English course was created to provide knowledge and skills to teach Academic English concisely, virtually, and effectively, adhering to MOOC requirements. This course is unique as its modules are organized to firstly go over basic skills required in Academic English, then introduce the relevant tasks in Academic English, and lastly present steps and tips in ensuring effective verbal and written Academic English performance. The presentation of the course encourages a smooth transition from understanding and applying basic skills to transferring these skills into Academic English reading, writing, and speaking. It is hoped that the ten (10) specifically crafted modules help learners to grasp Academic English faster and more effectively. Fundamental Academic English has the potential to serve as an essential blended learning material at pre-university and university level and provide necessary English language skills for university students to perform academically.